Highly selective fluorescence detection of Pd2+/4+ species based on a catalyzed aromatic Claisen rearrangement. Issue 128 (14th December 2015) - Li, Xuejing; Huang, Huanhuan; Zhu, Yuqing; Zhao, Hong; Wang, Zhifei
Abstract : A highly selective chemodosimeter based on 1, 8-naphthalimide for Pd 2+/4+ species via a Claisen rearrangement was developed with a detection limit of 1.4 μM. Abstract : A highly selective chemodosimeter based on 1, 8-naphthalimide for Pd 2+/4+ species via a Claisen rearrangement was developed, which not only discriminated Pd from competing Pt species, but also distinguished Pd in an oxidized state without altering its oxidation states from Pd 0 . Under optimized reaction conditions, the detection limit can reach 1.4 μM for Pd 2+ .